Materials information and mechanical response of TRIP/TWIP Ti alloys - Guohua Zhao (Nature Portfolio, 2021)
Abstract Materials innovation calls for an integrated framework combining physics-based modelling and data-driven informatics. A dislocation-based constitutive model accounting for both transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) was built to interpret the mechanical characteristics of metastable titanium alloys. Particular attention was placed on quantitatively understanding the composition-sensitive phase stability and its influence on the underlying deformation mechanism. For this purpose, a pseudoelastic force balance incorporating thermodynamics and micromechanics was applied to calculate the energy landscapes of β → α ″ martensitic transformation, {332}〈113〉 twinning and dislocation slip. Extensive material data were probed, computed and fed to the model. Our results revealed that TRIP and TWIP may operate simultaneously because of the presence of a noticeably overlapped energy domain, and confirmed {332}〈113〉 twinning is an energetically favourable deformation mechanism. The model validation further unveiled that the activation of β → α ″ transition remarkably enhances the strain-hardening and plasticity, even though the dynamically formed α ″ volume fraction is much less than that of deformation twinning. Our work suggests that the synchronised physical metallurgy and data-driven strategy allows to identify the compositional scenarios for developing high-performance engineering alloys.